The Myth of Forgiveness for Christians in the Gospel Johannes 19:29 and the Gospel John 19:30 (Roland Barthes Semiotic Frame) - Simorangkir, Imelda (Journal of Language Development and Linguistics, 2025)
The importance of Jesus as a holy figure, as well as the anguish and controversy that surrounded his death, have motivated us to conduct an interdisciplinary investigation of the events surrounding his crucifixion. As a result, this study will look at the crucifixion and death of Jesus through the linguistic. This research is to examine many signs contained in the Gospel of John 19:29 and the Gospel of John 19:30. This research will look at sour grapes as a signifier and sponge as a signified. Aside from that, the researchers would like to look into the hidden meaning or myth in the words "it is finished" that Christ said. This research employs Roland Barthes' semiotics to deconstruct the meaning of John' gospel. This research employed a descriptive qualitative approach. The approach used in this research is data reduction.